Fingerprint image segmentation using hierarchical technique - Wan Abu Bakar, Wan Aezwani; Sulong, Ghazali (2000)
Fingerprints are the ridge and furrow patterns on the tip or the finger and its verification is an important biometric technique (or personal identification). The quality or the fingerprint image is the most significant (actor in a reliable matching process. Thus, any pre-processing algorithm should aim to enhance the quality of the existing features without creating false features [I). This scenario brings the idea or the research. The research rocus on the segmentation approach. The purpose of the study is to identify a segmentation approach of fingerprint image by considering several approaches namely Hierarchical technique and Region growing by pixel aggregation technique. The process is vital when to apply next pre-processing stages i.e. thinning, identifying between true and false minutiae and minutiae extraction process. The research is supported by 50 samples or data that is collected through an available fingerprint device.